Rights and Responsibilities of Students with Disabilities in the Postsecondary Setting. Creating Employment Opportunities Project - Missouri Univ., Columbia. Dept. of Special Education; Missouri Univ., Columbia. Dept. of Special Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
This booklet addresses the provisions of the Rehabilitation Act of 1973 and the Americans with Disabilities Act of 1990 that impact on responsibilities and rights of postsecondary students with disabilities. The booklet discusses eligibility to receive academic adjustments, procedures for acquiring academic adjustments, grievance procedures in cases of disagreement with academic adjustments, the issue of confidentiality, "special privileges," eligibility for a course substitution or waiver, payment for academic adjustments, rights of international students, and strategies for self-advocacy. The booklet concludes with a list of six national resource organizations and three Missouri resource organizations. (JDD)
Sponsoring Agency: Office of Special Education and Rehabilitative Services (ED), Washington, DC.
Contract Number: H078C20011-92.
ERIC Note: A product of the Center for Innovations in Special Education.
Students.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Assistive Devices (for Disabled); Civil Rights; Civil Rights Legislation; College Students; Compliance (Legal); Disabilities; Educational Legislation; Eligibility; Federal Legislation; Higher Education; Student Personnel Services; Student Responsibility; Student Rights; Americans with Disabilities Act 1990 -- Missouri -- Rehabilitation Act 1973 (Section 504); Guides, Non-Classroom.